2018
DOI: 10.3390/bios9010006
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Monitoring of a UV Light-Assisted Biofunctionalization Protocol Using a Nanophotonic Biosensor

Abstract: A protocol for the covalent biofunctionalization of silicon-based biosensors using a UV light-induced thiol–ene coupling (TEC) reaction has been developed. This biofunctionalization approach has been used to immobilize half antibodies (hIgG), which have been obtained by means of a tris(2-carboxyethyl)phosphine (TCEP) reduction at the hinge region, to the surface of a vinyl-activated silicon-on-insulator (SOI) nanophotonic sensing chip. The response of the sensing structures within the nanophotonic chip was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Half-antiBSA-antibodies (haBSA) have been used as bioreceptors in this work, which reduces even more the distance between the sensor surface and the recognition sites, and provides a proper orientation of these recognition sites. This biofunctionalization process, as well as the protocol for obtaining the half-antibodies, was previously described in [910], where the light-assisted immobilization of the half-antibodies was monitored in real time and in-flow using the PBG sensing structures. However, the sensing performance obtained for those experiments was relatively low, mainly determined by the low irradiation efficiency obtained when illuminating the photonic chip with UV light through the fluidic elements used to perform the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Half-antiBSA-antibodies (haBSA) have been used as bioreceptors in this work, which reduces even more the distance between the sensor surface and the recognition sites, and provides a proper orientation of these recognition sites. This biofunctionalization process, as well as the protocol for obtaining the half-antibodies, was previously described in [910], where the light-assisted immobilization of the half-antibodies was monitored in real time and in-flow using the PBG sensing structures. However, the sensing performance obtained for those experiments was relatively low, mainly determined by the low irradiation efficiency obtained when illuminating the photonic chip with UV light through the fluidic elements used to perform the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The biofunctionalization of the photonic sensors using the light-assisted immobilization process developed by our group [910 13], started with a cleaning of the SOI photonic chip using piranha solution (H 2 SO 4 /H 2 O 2 = 1:3) for 20 min and a subsequent activation of its surface with O 2 plasma for 10 min. Then, the SOI chip was silanized by immersing it in 1% TEVS in Milli-Q water (pH adjusted to 8) for 1 h and finally curing it at 110 °C for an additional 1 h. The reduction process used to obtain the half-antibodies consisted on the incubation (90 min at 37 °C) of the BSA antibodies in acetate buffer (0.15 M sodium acetate, 0.01 M EDTA, 0.1 M sodium chloride, pH 4.5) at 4 mg/mL concentration in the presence of 25 mM tris(2-carboxyethyl)phosphine (TCEP).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on nano-modification based on AP has shown that they can be combined with nanoparticles (NPs) to form nanomaterials with novel properties, due to their advantages in molecular recognition and antibacterial activity. 15 , 17 , 18 Currently, quantum dots (QDs) not only have very important applications in solar cells and phototransistor components, but also in biological applications including biosensors, 19 , 20 bioimaging 21 and biomedical research. 22 Cadmium selenide (CdSe) QDs with a size of 1–20 nm are currently used for in vivo imaging and diagnostic treatment.…”
Section: Introductionmentioning
confidence: 99%